1994
DOI: 10.1021/ic00093a030
|View full text |Cite
|
Sign up to set email alerts
|

effect of Diverse Ligands on the Course of a Molecules-to-Solids Process and Properties of Its Intermediates

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. .) The different clusters form when different supporting phosphine ligands are employed. We report the syntheses, structures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 2 publications
1
32
0
Order By: Relevance
“…The spatial arrangement of the P atom is distorted tetrahedral. The PϪTe bond length of n -Bu 3 PTe [2.368 (1) Å ] compares well with those of t -Bu 3 PTe [2.368 (4) Å ] (Kuhn et al, 1987), i -Pr 3 PTe [2.366 (1) Å ] (Kuhn et al, 1990), and Me 2 P(Te)CH 2 CH 2 P(Te) Me 2 [2.357 (2) Å ] (Steigerwald et al, 1994) and points to 1.113 R 1 ( F ) (I > 2 σ (I)) 0.0307 wR 2 ( F 2 ) (all data) 0.0808 ( Δ / σ ) max < 0.001 Largest difference peak/hole, e Å -3 0.898/-1.479 Table 1 Crystal data and structure refinement of n -Bu 3 PTe.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…The spatial arrangement of the P atom is distorted tetrahedral. The PϪTe bond length of n -Bu 3 PTe [2.368 (1) Å ] compares well with those of t -Bu 3 PTe [2.368 (4) Å ] (Kuhn et al, 1987), i -Pr 3 PTe [2.366 (1) Å ] (Kuhn et al, 1990), and Me 2 P(Te)CH 2 CH 2 P(Te) Me 2 [2.357 (2) Å ] (Steigerwald et al, 1994) and points to 1.113 R 1 ( F ) (I > 2 σ (I)) 0.0307 wR 2 ( F 2 ) (all data) 0.0808 ( Δ / σ ) max < 0.001 Largest difference peak/hole, e Å -3 0.898/-1.479 Table 1 Crystal data and structure refinement of n -Bu 3 PTe.…”
mentioning
confidence: 52%
“…The distortion is reflected by the mean TeϪPϪC and CϪPϪC angles [112.9(1) ° and 105.9(1) ° ] that are in good agreement with those of Me 2 P(Te)CH 2 CH 2 P(Te)Me 2 [113.5(3) ° and 105.2(4) ° ] (Steigerwald et al, 1994). In contrast, the mean TeϪPϪC and CϪPϪC angles of t -Bu 3 PTe [108.7(4) ° and 110.2(5) ° ] (Kuhn et al, 1987) and i -Pr 3 PTe [110.9(1) ° and 110.7 (1) ° ] (Kuhn et al, 1990) are much closer to the ideal tetrahedral angle of 109.3 ° .…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…So far, the only structurally characterized ditelluro R 2 P(Te)(CH 2 ) n P(Te)R 2 compound is Me 2 P(Te)(CH 2 ) 2 -P(Te)Me 2 , which was not prepared by direct oxidation by elemental tellurium, but by a tellurium transfer reaction between Et 3 PTe and Me 2 P(CH 2 ) 2 PMe 2 . 9 In the case of structurally analogous R 2 PNHPR 2 compounds (R ¼ alkyl, aryl), a monotelluro P-H tautomer iPr 2 P(Te)NP(H) iPr 2 was successfully prepared by reaction of iPr 2 PNHPiPr 2 with elemental tellurium. 10 The synthesis of ditelluro salts TME-DA$Na[R 2 P(Te)NP(Te)R 2 ] was again successful when using the deprotonated [R 2 PNPR 2 ] À species (R ¼ iPr, 11 tBu, 12 Ph 13 ) as starting materials.…”
mentioning
confidence: 99%
“…The control over the stoichiometric ratio, combined with the kinetic control, which derives from low activation energies of these processes, could allow the synthesis of otherwise inaccessible solid phases or microinhomogeneous materials such as nanocomposites. 2 Despite the synthetic potential of the phosphine selenides, their reactions with metal carbonyls have been explored only to a limited extent prior to the last three years and, in general, most of the previously described chalcogenido-carbonyl clusters containing Group 15 donor ligands had been obtained by substitution reactions. 3 As regards chelating diphosphine selenides, we have recently found that the reactions of [Fe 3 (CO) 12 ] with three diphosphine diselenides dppmSe 2 , dppeSe 2 and dppfcSe 2 produce the substituted 50-electron, nido clusters Fe, dppfc) as the main products.…”
mentioning
confidence: 99%